TOWARDS SUSTAINABLE FISHING: ENERGY CONVERSION EFFICIENCY OF BALI’S FISHING BOATS - Nugraha, I Made Aditya; Desnanjaya, I Gusti Made Ngurah (Universitas Mataram, 2025)
Energy efficiency in small-scale fishing boats has become a critical issue due to their high dependence on fossil fuels, rising operational costs, and environmental impacts. Fishing boats less than 5 GT generally operate with fluctuating engine loads, potentially reducing energy conversion performance. This study aims to analyze the energy conversion efficiency of fishing boats operating in Bali Province. The research method uses a descriptive-quantitative approach through field studies. Primary data were obtained from measurements of fuel consumption, engine power and speed, electrical load, and operating duration at each stage of the boat's activities, while secondary data came from technical documents and operational logbooks. Efficiency analysis was conducted by comparing the input energy from diesel fuel and the output energy in the form of mechanical and electrical energy. The results show that energy consumption is dominated by the propulsion system, especially during the cruising phase. The total energy conversion efficiency is still relatively low, ranging from 22%–30%, and decreases during the maneuvering and fishing phases due to partial engine loads. These findings suggest that improvements in operational efficiency and engine maintenance are needed to reduce fuel consumption, reduce operational costs, and support the aspirations of small-scale fishing.